Simulation Analysis of Residual Stresses in Spiral Bevel Gear Machining Based on an Oblique Cutting Model - Wang Hao; Zhang Fengshou; Jiang Chuang (Jixie chuandong)
In this study, milling large wheels for spiral bevel gears by the profile method, the effect of cutting speed, depth of cutting and feed rate on the residual stress on the machined surface is studied. According to the characteristics of spiral bevel gears machined by the forming method, a three-dimensional simulation model of bevel cutting is established to simulate the cutting process of gears, and the effects of cutting speed, feed rate, depth of cutting and coolant on the residual stresses on the surface of the workpiece are simulated using the single factor method. The simulation results show that the residual stresses on the machined surface of the spiral bevel gear are distributed in a "spoon" pattern along the depth of cut, the residual tensile stresses are on the surface, and the residual compressive stresses are on the sub-surface. The surface residual tensile stress increases with the increasing feed rate and cutting speed, the layer depth of residual stress deepens with the increasing feed, and the depth of cut has no significant effect on the residual stress. The addition of coolant reduces the residual tensile stress on the surface. Through this research, a theoretical reference is provided for the analysis of residual stresses in the cutting of spiral bevel gears.